Influence of alcohols/electrolytes on the interaction of reactive red dye with surfactant and removal of dye from solutions. Issue 5 (October 2019) - Mahbub, Shamim; Shahriar, Imrul; Iqfath, Mushfeqa; Hoque, Md. Anamul; Halim, Mohammad A.; Khan, Mohammed Abdullah; Rub, Malik Abdul; Asiri, Abdullah M.
Abstract: Interactions of anionic textile dye -reactive red (RR) with cetyltrimethylammonium bromide (CTAB), a cationic surfactant in the absence as well as the presence of different electrolytes and alcohols of different concentrations have been studied with the help of UV–vis spectroscopy and molecular dynamics simulation. The dye-surfactant binding was observed to be taken place at a concentration of the surfactant far below cmc (generally cmc varies from 0.9 mM to 1.2 mM). The binding of dye and surfactant was reflected by a significant change in λmax with the appearance of splitting of the band in the spectrum of the dye. The binding constant ( Kb ) of complexation was executed by means of the Benesi-Hildebrand plot. The binding constant ( Kb ) of RR-CTAB complexes increased with increasing concentration of dye, concentration of electrolytes added, dielectric constant and pH of the medium. The values of binding constant for RR-CTAB system dwindled with the enhancement of the temperature. TheΔ G 0 values of the complexes were found to be negative which indicate that complex formation was thermodynamically spontaneous. The negative values of Δ H 0 indicate that the complexation process is exothermic and positive values of Δ S 0 indicate that RR-CTAB complexation is both an enthalpy & entropy governed phenomena. The dye can be effectively removed from the waste water by the interaction of dye with surfactant in presence of salt of higher concentration and 30% ethanol. Moreover, MD simulations provided a detailed analysis of the mechanism of interaction between the dye and surfactant molecules.